Results of watchful waiting of unruptured intracranial aneurysms in a Western patient population: a single-center cohort. (5th November 2021) - Aubertin, Mathilde; Jourdaine, Clément; Thépenier, Cédric; Labeyrie, Marc-Antoine; Civelli, Vittorio; Saint-Maurice, Jean-Pierre; Guédon, Alexis; Houdart, Emmanuel
Abstract : Background: The natural history of unruptured intracranial aneurysms (UIAs) in Western populations is still debated, especially for those <7 mm. Reporting data of a large single-center cohort managed with watchful waiting is therefore interesting. Methods: From January 2011 to June 2019, 662 UIAs were followed up by yearly MR angiography. Morphologically stable UIAs were managed conservatively while unstable UIAs were offered treatment. The patients' clinical and radiological data were analyzed retrospectively. Results: UIAs were ≤4 mm in 60%, 4.1–7.0 mm in 33%, and >7 mm in 7%. They were located on the anterior circulation in 90% of cases. The mean follow-up duration was 51.32 months for a total of 2831 aneurysm-years. During follow-up, 37 UIAs (5.5%) were treated because of an increase in size, and 8 UIAs were treated because of patient decision. Three aneurysms ruptured during follow-up for an annual risk of rupture of 0.1% (95% CI 0% to 0.24%). No risk factors for rupture were identified. The three ruptured cases made an excellent recovery. During follow-up, annual mortality from unrelated causes was 0.8% (95% CI 0.51% to 1.18%). Conclusions: This single-center cohort evaluated our watchful waiting policy applied in two-thirds of all incidental UIAs. Morphological change of UIAs during follow-up led to treatment in 5.5% of cases. With such a management paradigm, we found a low rupture rate in these selected UIAs and the mortality was unrelated to aneurysms.